A phenomenological model for investigating unequal planet load sharing in epicyclic gearboxes. (1st January 2020) - Liu, Zongyao; Lei, Yaguo; Liu, Huan; Yang, Xiao; Song, Wenlei
Highlights: A phenomenological model is proposed for investigating unequal planet load sharing in epicyclic gearboxes. Modulation sidebands in the spectrum caused by unequal load sharing are explained based on the phenomenological model. Unequal planet load sharing has a large influence on the spectral structures. The phenomenological model is validated by three experiments on an epicyclic gearbox test rig. Abstract: Vibration signals of epicyclic gearboxes often present abundant modulation sidebands in the spectrum, and investigations of these sidebands are helpful for the understanding of vibration mechanism and fault diagnosis of epicyclic gearboxes. In epicyclic gearboxes, both the carrier rotation and unequal load sharing among planets can lead to abundant sidebands near the meshing frequency. Modulation sidebands due to the carrier rotation have been extensively investigated, while additional sidebands caused by unequal load sharing among planet gears are seldom studied. Aiming at this issue, a phenomenological model of vibration signals of epicyclic gearboxes is developed considering unequal planet load sharing conditions. In this model, an angular shift of a planet gear is assumed to simulate the manufacturing or assembly errors in gearboxes, and different load sharing ratios among planets are calculated. After that, spectral structures of vibration signals of epicyclic gearboxes under unequal load sharing conditions are derived from the phenomenological model. Through the deduced results, it is shown that unequal planet load sharing can influence the spectral structures largely and the formation mechanisms of some additional sidebands in the spectrum are explained. Finally, experiments under three health conditions, i.e., healthy, cracked sun gear and cracked planet gear, are conducted on an epicyclic gearbox test rig. The effectiveness of theoretical deductions of phenomenological models is validated by the collected vibration signals from the test rig.